2007
DOI: 10.1002/macp.200700166
|View full text |Cite
|
Sign up to set email alerts
|

On‐Line HPLC‐NMR of PS‐b‐PMMA and Blends of PS and PMMA: LCCC‐NMR at Critical Conditions of PS

Abstract: Blends and copolymers of PS and PMMA were analysed by LC coupled to 1H NMR at the critical point of adsorption. The separation of the polymers was achieved at chromatographic conditions that correspond to the critical point of PS and the size‐exclusion mode of PMMA. Copolymers and blends were analysed by on‐line coupled 1H NMR. For the homopolymer blends, separation into the components was achieved, while the copolymers were separated with regard to the block lengths of the PMMA blocks. The tacticity of the PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…Thus, information concerning specific copolymer parameters such as the average molar masses $\overline{M}_{\rm n}$ and $\overline{M}_{\rm w}$ , the polydispersity and the distributions of microstructures is of great importance since these parameters have influence on the copolymer behavior. Recent developments in the coupling of different chromatographic techniques with NMR spectroscopy give access to these parameters very easily 2–6…”
Section: Introductionmentioning
confidence: 99%
“…Thus, information concerning specific copolymer parameters such as the average molar masses $\overline{M}_{\rm n}$ and $\overline{M}_{\rm w}$ , the polydispersity and the distributions of microstructures is of great importance since these parameters have influence on the copolymer behavior. Recent developments in the coupling of different chromatographic techniques with NMR spectroscopy give access to these parameters very easily 2–6…”
Section: Introductionmentioning
confidence: 99%
“…13b. [50] with permission). LCCC, liquid chromatography at critical conditions; NMR, nuclear magnetic resonance; PS, polystyrene.…”
Section: Microstructure Analysis By Column-based Fractionationsmentioning
confidence: 94%
“…Using an octadecyl-modified silica gel as the stationary phase and an eluent of acetonitrile-deuterium oxide 50:50 (v/v) the sample was separated into different functionality fractions that were then analyzed by on-flow 1 H-NMR. In a number of very recent publications it was shown that LC-NMR was used successfully for the analysis of polymer blends and block copolymers regarding chemical composition and microstructure [159,160]. The critical point of adsorption was also used for the analysis of tacticity of poly(ethyl methacrylate)s by HPLC-NMR [157].…”
Section: Coupling With 1 H-nmrmentioning
confidence: 99%